Hydroecological effects of mining and its restoration ways in coal mining areas of Western China - Hao WANG; Qiangmin WANG; Shuning DONG; Xiaodong WANG; Guangrong GE; Xiyu ZHANG; Shumiao CAO; Quan ZHANG (Meitan xuebao)
The mining areas in arid and semi-arid region have become important coal production bases to ensure China’s energy strategic security, however, coal development by large-scale and high-intensity mining has triggered a series of water resources and ecological environment problems. The article analyzes ecological issues from a hydrological perspective, systematically reveals the hydrological and ecological effects caused by coal mining, and develops restoration technologies for damaged hydrological ecology in mining areas based on water. The research results are indicated by the follow. The subsidence caused by coal mining accelerates the infiltration and evaporation of precipitation, and the soil moisture near the soil fractures appears “funnel zone”. The water conducting fracture connects directly with the loose aquifer in typical coal areas, and the groundwater flow field and resource quantity have undergone significant changes. The maximum water level drop exceeds 14 m, the average water level drop exceeds 5m, and the amount of negative balance exceeds 2500×104 m3/a. The decrease in groundwater level leads to a gradual reduction in river flow, with a maximum of 172×104 m3/a. In areas where the groundwater level is less than 5 m, the decrease in groundwater level significantly reduces the ecological water consumption of vegetation. Base on the water resources and ecological environment problems, the hydrological and ecological restoration technologies have been developed, to response to the current situation of water resource shortage, ecological water level reduction, poor soil water retention, and low vegetation water use efficiency. Firstly, the moderate purification technology for mine water by nanofiltration has been developed. The technology has a wide range of desalination rates, and the treated mine water can provide high-quality water sources for hydrological and ecological restoration. Secondly, the ecological reinjection technology has been developed in soil, basing on the large amount of mine water inflow, good mine water quality, and considerable storage space in the Quaternary loose aquifer. The mine water recharge can lift the ecological water level in the mining area. Thirdly, the soil reconstruction technology has been developed, in which a water-resistant soil layer is placed underneath the vegetation root soil layer, which can significantly increase soil moisture and vegetation water consumption in the collapsed area. Fourthly, soil microbial inoculation technology has been developed, and appropriate inoculation treatment can expand the absorption range and area of soil moisture and nutrients by roots, regulate the expression of genes related to photosynthesis, sugar metabolism, glutathione metabolism, and calcium ion signal transduction, and improve the water efficiency and drought resistance of vegetation. The research results provide scientific basis for water resource protection and ecological environment restoration in arid and semi-arid mining areas in western China.